2018
DOI: 10.3390/su10113949
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Factors Influencing the Activity Spaces of Bikeshare around Metro Stations: A Spatial Regression Model

Abstract: Metro-bikeshare integration is considered a green and efficient travel model. To better understand bikeshare as a feeder mode to the metro, this study explored the factors that influence the activity spaces of bikeshare around metro stations. First, metro-bikeshare transfer trips were recognized by matching bikeshare smartcard data and metro smartcard data. Then, standard deviation ellipse (SDE) was used for the calculation of the metro-bikeshare activity spaces. Moreover, an ordinary least squares (OLS) regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Three clusters are obtained. The Cluster 1 includes station 4; Cluster 2 contains the station 1, 5, 6, 7, 8, 28, 29, 32, and 33; Cluster 3 includes station 3,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,30, and 31. Different clusters are marked in Figure 1.…”
Section: Usage Patterns Of Dlbs Near Stations In Different Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Three clusters are obtained. The Cluster 1 includes station 4; Cluster 2 contains the station 1, 5, 6, 7, 8, 28, 29, 32, and 33; Cluster 3 includes station 3,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,30, and 31. Different clusters are marked in Figure 1.…”
Section: Usage Patterns Of Dlbs Near Stations In Different Areamentioning
confidence: 99%
“…The distance people ride varies from workdays to weekends. Ma et al [15] revealed that the average activity distance of metro-bike-sharing on weekends was smaller than that on weekdays in Nanjing, China. Moreover, the distance of using bicycles in different areas of the same city should be different, such as the city center and suburbs, because the land use characteristics and population density of different areas of the city are different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago, only station-based bike-sharing was available, and people must use a smart card to unlock, use, and pay for it, and the associated registration process is overly complicated. But dockless bike-sharing has gradually replaced station-based bike-sharing in numerous Chinese cities [38][39][40][41]. The implementation of smartphone payments has been the norm in today's China, substantially simplifying the previously complicated registration process.…”
Section: Discussionmentioning
confidence: 99%
“…As a healthy and low-cost way to travel, BS has been widely studied by researchers [3,[5][6][7][8][9][10][11][12][13]. Simultaneously, many studies have shown that DBS has a great impact on other modes.…”
Section: Introductionmentioning
confidence: 99%